Music video application development using android - Lim, Yu Wen (2021)
This project is mainly about the development of a music video application using Android. It is also known as a media player that works on the Android native operating system. In this project, it will be able to get the music or video from the local storage of smartphone devices and list down the music and video. Besides that, it also consists of three ways to control the music player which are button click, voice command, and swipe gesture. With these ways, users can control the music player easily as they just need to speak out some specific command to control the music player. For the video player, the user can easily view the video in portrait or landscape mode. The user also can enlarge the video view into a full screen to have a better view. However, there are some user interfaces of the existing mobile application that are functional but very messy at the same time. Therefore, this project will design a simple, clean and clear interface to solve this problem and let users have a better user experience. Furthermore, the methodology of system analysis and design to develop this project is Mobile Application Development Life Cycle (MADLC). Mobile Application Development Life Cycle consists of six phases which are Planning, Design, Development, Testing, Release, and Maintenance. With the help of these six phases in the Mobile Application Development Life Cycle, the development of this project will be smoother and can minimize the bugs during the developing and testing stage.